McBride, Ernie (audio interview #1 of 1) - McBride, Ernie (11/12/1909 - 5/5/2007); Johnson, Polly, interviewer; Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This single interview was conducted by two members of the Long Beach Cultural Heritage Commission and the information collected in this interview was used to nominate McBride's house as a local landmark. The interview was conducted in McBride's home. 7/27/1994